German mobile apps for patients with psoriatic arthritis: systematic app search and content analysis : original article/research - Groß, Georg; Lull, Christian; Ahnen, Jan von; Olsavszky, Victor; Knitza, Johannes; Schmieder, Astrid; Leipe, Jan (Health policy and technology, 2022)
Background - Psoriatic arthritis (PsA) is a chronic musculoskeletal disease. Functional limitations result in significant patient burden. The use of smartphone apps to complement medical treatments could increase patients’ adherence resulting in better clinical outcome and consequently increased quality of life. - Objective - This study aimed to assess and compare currently available smartphone apps for PsA patients using a standardized rating scale. - Methods - We conducted a systematic screening of apps for PsA patients in German App Stores and selected apps meeting inclusion criteria: availability in both app stores, German or English language, relevant for patients with psoriatic arthritis, not developed for congress use or clinical studies, no fee-based apps. Three reviewers evaluated apps using the Mobile Application Rating Scale (MARS). Analysis included technical features and mean scores as well as interrater agreement and linear regression. The best-rated app was then rated by PsA patients. - Results - Among 232 screened apps, 8 met all inclusion criteria. The app “Rheuma-Auszeit” scored highest with a healthcare provider MARS rating of 4.4 and a patient userMARS rating of 3.7. Subjective quality was lower for all apps. App store star ratings and MARS ratings were not significantly correlated (P=0.34). No app was Conformité Européenne (CE) certified and no underlying clinical studies were found. - Conclusions - App quality was heterogenous and generally low. Star ratings - the only accessible tool for patients - does not suffice to identify high-quality apps. We suggest involving patients in development of apps. Since patients and physicians have different perceptions of app quality, we recommend a joint development and evaluation process.
Online erhältlich: 13 November 2022, Artikelversion: 18 November 2022
Gesehen am 06.06.2023